A multiple indicator, multiple cause method for representing social capital with an application to psychological distress - Congdon, Peter (Journal of geographical systems, 2010)
This paper describes a structural equation methodology for obtaining social capital scores for survey subjects from multiple indicators of social support, neighbourhood and trust perceptions, and memberships of organizations. It adjusts for variation that is likely to occur in levels of social capital according to geographic context (e.g. level of area deprivation, geographic region, level of urbanity) and demographic group. Social capital is used as an explanatory factor for psychological distress using data from the 2006 Health Survey for England. A highly significant effect of social capital in reducing the chance of psychiatric caseness is obtained after controlling for other individual and geographic risk factors. Allowing for social capital has considerable effects on the impacts on psychiatric health of other risk factors. In particular, the impact of area deprivation category is much reduced. There is also evidence of significant differentiation in social capital between population categories and geographic contexts.